Use of high pressure oxygen to remove nasal foreign body - Devkota, AR; Yadav, P (Journal of Institute of Medicine Nepal, 2008)
Case report: Use of an innovative and simple technique of removing foreign body from nose using high pressure oxygen is reported. Key Words: High pressure oxygen, nasal foreign body, impacted slippery foreign body The full text of this paper is available at Journal of Institute of Medicine website